Analisis Kemampuan Literasi Numerasi Pada Siswa Kelas Ill SDI Padhapae Di Desa Raja Timur (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Literacy and numeracy skills are the ability to find various kinds of numbers and symbols in basic mathematics, the ability to analyze the information displayed, and the ability to interpret answer results. This research method is descriptive research with a qualitative approach. This research aims to determine students' abilities towards numeracy literacy in solving problems. Data collection techniques use test, interview and documentation methods. The analysis techniques used are data reduction, data presentation, and drawing conclusions. This research was conducted on 3rd grade students at SDI Padhapae, totaling 15 people, 8 men, 7 women. Based on the results of tests conducted on 15 students, 5 out of 15 students had a low level of numeracy literacy, because the students had difficulty solving questions related to everyday life. There are 6 students who can be put into the medium category because there are difficulties faced by students in solving problems, namely difficulty in working on the story problems given, but students can already use their reasoning to solve a given mathematical problem. Then there were 4 students in the high numeracy literacy category. They already understood the questions given and had no difficulty when asked to relate everyday life to mathematical concepts.